Ants (Hymenoptera: Formicidae) in five hospitals of Porto Alegre, Rio Grande do Sul State, Brazil = Formigas (Hymenoptera: Formicidae) em cinco hospitais de Porto Alegre, Rio Grande do Sul, Brasil. - Flávio Roberto Mello Garcia; Carolina Charlier Ahlert; Bianca Ribeiro de Freitas; Maura Morel Trautmann; Simone Pirotta Tancredo; Junir Antonio Lutinski (Universidade Estadual de Maringá, 2011)
The presence of ants in hospitals is health risk for the hospital community, since presents a strong capability to carry pathogenic organisms throughout this environment. This study was carried out from May 2007 to April 2008, aiming the identification of ant species that infest the hospitals in Porto Alegre, Rio Grande do Sul State, Brazil. A total of 989 ants from 19 species were sampled: Acromyrmex niger (Fr. Smith, 1858), Brachymyrmex sp., Camponotus rufipes (Fabricius, 1775), Camponotus sericeiventris (Guerin-Meneville, 1838), Camponotus sp1, Camponotus sp2, Gnamptogenys sp., Hypoponerasp., Labidus coecus (Latreille, 1802), Monomorium pharaonis (Linnaeus, 1758), Pachycondyla sp., Paratrechina fulva (Mayr, 1862), Paratrechina longicornis Latreille, 1802, Pheidole sp1, Pheidole sp2, Pheidole sp3, Pheidole sp4, Pheidole sp5, and Tapinoma melanocephalum Fabricius, 1793. Among them, Brachymyrmex sp. was the most frequent one (47.0%) followed by Monomorium pharaonis (18.7%) and Labidus coecus (17.2%). A presença de formigas em hospitais constitui risco à saúde da comunidade hospitalar, uma vez que elas possuem o poder de carrearmicrorganismos patogênicos por este ambiente. Este estudo foi realizado no período de maio 2007 a abril de 2008, com o objetivo de identificar as espécies de formigas que infestam hospitais em Porto Alegre, Brasil. Foi coletado um total de 989 formigas pertencentes a 19 espécies, sendo: Acromyrmex niger (Fr. Smith, 1858), Brachymyrmex sp., Camponotus rufipes (Fabricius, 1775), Camponotus sericeiventris (Guerin-Meneville, 1838), Camponotus sp., Camponotus sp.2, Gnamptogenys sp., Hypoponera sp., Labidus coecus (Latreille, 1802), Monomorium pharaonis (Linnaeus, 1758), Pachycondyla sp., Paratrechina fulva (Mayr, 1862), Paratrechina longicornis Latreille, 1802, Pheidole sp., Pheidole sp.2, Pheidole sp.4, Pheidole sp.5, Pheidole sp.7 e Tapinoma melanocephalum Fabricius, 1793. Destas, Brachymyrmex sp. foi a mais frequente com 47,0%, seguida por Monomorium pharaonis com 18,7% e Labidus coecus com 17,2%.